PENERAPAN AKUNTANSI INFAQ SHODAQOH BERDASARKAN PSAK 109 di YDSF AL-FALAH SIDOARJO - Mita Khusnul Desiana; Soesilawati Soema Atmadja (Ekomania, 2023)
This research was created with the aim to find out how true in the application of zakat accounting in accordance with PSAK 109 which is a guideline for the preparation of financial statements that are applied to the Amil Zakat Institute of Al-Falah Social Fund Foundation (YDSF) Sidoarjo, so that the standard of financial statements that are able to have good accountability and transparent information that is fulfilled karne in the future report can be held accountable from the processing of the parties amil k epada people who have trusted to distribute zakat funds ( muzzaki). The type of research applied is qualitative with data obtained using interview methods, as well as observations. Yayasan Dana Sosial Al-Falah Sidoarjo has been good to apply PSAK 109 in terms of recognition, measurement and disclosure although it is still not perfect as it has been applied in accordance with PSAK 109 and still has to be in the process of adjustment. In terms of the presentation of financial statements from the Al-Falah Sidoarjo Social Fund Foundation still does not meet the standards that have been made by IAI in the form of psak 109 rules, although Yayasan Dana Sosial Al-Falah Sidoarjo already has a monthly financial report to be submitted to muzzakinya as a form of financial information and responsibility for the form of financial flow transparency, but the making of reports that have been regulated in PSAK 109 obliges to each organization amil zakat u to make a report that has been arranged on its contents, which consists of several accounting bookkeeping standards, namely, Financial Position Report, Fund Change Report, Asset Management Report, Cash Flow Statement, and Notes on Financial Statements, so that in this case can realize perfect accountability in its management.